ANALISIS UPAYA PENEGAKAN HUKUM DAN PENGAWASAN MENGENAI KEBAKARAN HUTAN DI KALIMANTAN BARAT - Johanna Griselda Joy Saputro; I Gusti Ayu Ketut Rachmi Handayani; Fatma Ulfatun Najicha (Republic of Indonesia Defense University, 2021)
This study aims to examine the factors that cause forest fires in West Kalimantan Province, the impact caused by forest fires in West Kalimantan Province, and law enforcement and monitoring efforts are carried out on cases of forest fires in West Kalimantan Province. The type of research used by the author in conducting this legal research is empirical legal research. Forest fires are a natural phenomenon that often occurs in Indonesia. The main reason is because Indonesia is located on the equator so that it has a tropical climate. This condition has an impact on natural conditions in Indonesia, especially Kalimantan, because Kalimantan is an area that has a large forested area so that during the long dry season it often experiences fires caused by many factors such as rubbing twigs to the intention of the community and individuals to throw cigarette butts into the forest area for a fire to occur. Law enforcement and supervision from the central and regional governments are very necessary as an effort to protect forests for the balance of the surrounding environment and the sustainability of living things in the future.